Description of a new species of Lasiocesa Koçak from miombo woodlands in Malawi (Lepidoptera, Lasiocampidae, Lasiocampinae, Pinarini) - Revay, Edita E.; Prozorova, Tatiana A.; Junnila, Amy; Yakovlev, Roman V.; Saldaitis, Aidas; Volkova, Julia S.; Sulak, Harald; Müller, Günter C.; Prozorov, Alexey M. (Zootaxa, 2025)
New Lasiocesa Koçak, 2013 species, Lasiocesa ladislavi sp. nov., is described from the Central Zambezian wet miombo woodlands ecoregion of Malawi. The new species is compared with four other known Lasiocesa species. Adults, their genitalia, distribution maps and photos of the habitat of the new species are illustrated.